The Role of DPPPAPM Makassar in Child Protection for Eska Victims from the Perspective of Islamic Law - Rasyid, Andi Rasniwati; Talli, Abd. Halim; Fatmawati (Jurnal Mercusuar, 2022)
Legal protection for children is stipulated in Law No. 35 of 2014 concerning Child Protection. Article 13 paragraph (1) states that every child who is under the care of parents, guardians, or any other responsible parties has the right to protection from discriminatory treatment, exploitation, neglect, cruelty, violence, abuse, injustice, and other forms of mistreatment. Sexual exploitation of children in Indonesia is estimated to affect between 40,000-150,000 children per year based on a UNICEF survey. This research aims to uncover and explain the role of the Makassar City Women’s Empowerment, Child Protection, and Community Empowerment Office in providing legal protection for victims of commercial sexual exploitation of children from an Islamic legal perspective. This is a qualitative research with a juridical-legal approach. Primary data sources in this study were obtained through interviews with the Makassar City Women’s Empowerment, Child Protection, and Community Empowerment Office, while secondary data sources were obtained from various laws and literature related to the subject. Data analysis was conducted by displaying data, reducing data, editing data, analyzing data, and drawing conclusions/verifying. The results show that the Makassar City Women’s Empowerment, Child Protection, and Community Empowerment Office provide protection through three programs, namely child-friendly cities, citizen shelters, and the formation of a trafficking group that prioritizes children’s welfare.